2022
DOI: 10.1186/s12879-022-07678-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of multidrug-resistant ESKAPEE pathogens from clinical samples in Chonburi, Thailand (2017–2018)

Abstract: Background ESKAPEE pathogens Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter spp. and Escherichia coli are multi-drug resistant (MDR) bacteria that present increasing treatment challenges for healthcare institutions and public health worldwide. Methods 431 MDR ESKAPEE pathogens were collected from Queen Sirikit Naval Hospital, Chonburi, Thailand between 2017 and 2018.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In addition to Gram-negative pathogens, four Gram-positive bacterial pathogens − E. faecalis, E. faecium, S. aureus, and S. pneumoniae − were analyzed (Table 1), though it is worth nothing that S. pneumoniae represents our smallest Bayesian network (10 nodes). To assess the accuracy of our system, the Bayesian networks were initially analyzed for the presence of previously observed co- resistance patterns, including the co-occurrence of phenicol and lincosamide resistance genes (38,52). In S. aureus , the phenicol resistance gene fexA exhibited an overall positive probability of co- occurrence with the lincosamide resistance gene lnuB (cond.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Gram-negative pathogens, four Gram-positive bacterial pathogens − E. faecalis, E. faecium, S. aureus, and S. pneumoniae − were analyzed (Table 1), though it is worth nothing that S. pneumoniae represents our smallest Bayesian network (10 nodes). To assess the accuracy of our system, the Bayesian networks were initially analyzed for the presence of previously observed co- resistance patterns, including the co-occurrence of phenicol and lincosamide resistance genes (38,52). In S. aureus , the phenicol resistance gene fexA exhibited an overall positive probability of co- occurrence with the lincosamide resistance gene lnuB (cond.…”
Section: Resultsmentioning
confidence: 99%
“…Cells stained with fluorescent nucleic acid stain SYTO 9 and PI exhibited green and red fluorescence, respectively. , SYTO 9 stains living and dead cells, and PI stains the DNA nucleus, emitting red fluorescence after embedding double-stranded DNA. PI is often used to detect apoptosis. , Compared with the LB broth control group and the monotherapy group, the combination group exhibited an increased red fluorescence, thereby indicating an increase in bacterial cell membrane permeability during early growth (2 h) (Supporting Figure S2). The CLSM result revealed that in the combination group, the red fluorescence was significantly enhanced, which indicated that a large amount of PI entered the cells and bound to the DNA (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…PI is often used to detect apoptosis. 24,25 Compared with the LB broth control group and the monotherapy group, the combination group exhibited an increased red fluorescence, thereby indicating an increase in bacterial cell membrane permeability during early growth (2 h) (Supporting Figure S2). The CLSM result revealed that in the combination group, the red fluorescence was significantly enhanced, which indicated that a large amount of PI entered the cells and bound to the DNA (Figure 5).…”
Section: ■ Resultsmentioning
confidence: 99%
“…The range of pathogens used in HHRR was confined to the ESKAPE pathogens as well as any contig annotated as Enterobacteraciae. This was done to include Escherichia coli (as in the “ESKAPEE”) [26, 27] as well as to ensure that contigs without complete taxonomic annotations but which are likely derived from the ESKAPE organisms would be captured. This is common for contigs originating from ESKAPE-associated plasmids and MGEs [28, 29].…”
Section: Methodsmentioning
confidence: 99%